Comunidade fitoplanctônica do reservatório de Barra Bonita e sua relação com a composição e quantidade de polissacarídeos extracelulares e agregados gelatinosos - Dellamano-Oliveira, Maria José (2006)
(Gelatinous aggregates (lake snow) from an eutrophic Brazilian reservoir and their relationships with abundant phytoplanktonic algae). Lake snow and phytoplankton studies were conduced in Barra Bonita Reservoir, in the Tietê River basin, southeastern Brazil. Monthly sampling from April 2002 to January 2004 and two intensive sampling (dry and wet periods) were performed in six depths (0m, 1m, 3m, 5m, 10m and 17m deep), at a sample station localized 3km upstream the reservoir dam. Among the sampled months the highest numbers of aggregates were registered in August 2002 (167 agg.L-1) and September 2002 (230 agg.L-1). The mean numbers of aggregates registered in the intensive samplings was 38 agg.L-1 in June 2003 and 68 agg.L-1 in December 2003. Seasonal occurrence of algal species aggregated to polysaccharidic matrices followed the dynamic of dominant species in the Reservoir. Aulacoseira granulata and free cells of Microcystis sp. were the most frequent taxa in the aggregates (70%) in the majority of samples. Other species, as Pseudanabaena mucicola, Microcystis aeruginosa, Planktothrix tropicalis, Cyclotella menegheniana, Cryptomonas sp, Actinastrum hantzschii, Quadrigula lacustris and Schroederia indica were registered in less frequency (10% to 15%). The monosaccharide composition of the gelatinous aggregated polysaccharides was the same registered in dissolved carbohydrates samples, reinforcing the importance of phytoplankton as the major source, chiefly of polysaccharides and of the gelatinous aggregates in the transport of these sugars through the water column. However, studies concerning gelatinous aggregates in freshwater are recent and more investigation are needed to confirm the patterns showed in our results.